Profits: A Case Of Exchange Rate Volatility - Gatut L Budiono; Agnesya Firdayasa (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2017)
The purpose of this research was to measure theeffect of exchange ratevolatility on the companies’ profit in food and beverages sub sector with revenue andexpenses as an intervening. The analysis technique used in this research was regressionand path analysis. The financial statement and middle exchange rate of first quarter of 2012 to2015 third quarter IDX and BIsecondary data was incorporated in the research.These research result showed that the exchange rate volatility may affect companies’profit in food and beverages sub sector either directly or indirectly.